Dakotaseps gen. nov., a replacement name for the lizard genus Dakotasaurus Nydam 2013, a junior homonym of the ichnotaxon Dakotasaurus Branson and Mehl 1932 - Nydam, Randall L (Zootaxa, 2014)
Dakotasaurus gilletorum Nydam 2013 was erected for two partial mandibles of a paramacellodid-cordylid grade scincomorphan lizard from the early Late Cretaceous (Cenomanian) of southern Utah (Nydam 2013). However, the genus name Dakotasaurus is a junior homonym of the ichnofossil Dakotasaurus Branson and Mehl 1932. Under Article 23.1 of the International Code of Zoological Nomenclature (ICZN 1999) Branson and Mehl’s (1932) name has priority.